Situational analysis of diabetic retinopathy treatment Services in Ghana - Agatha Mensah-Debrah; Kwesi Nyan Amissah Arthur; David Ben Kumah; Kwadwo Owusu Akuffo; Isaiah Osei Duah; Covadonga Bascaran (BMC, 2021)
Abstract Background Although the equitable distribution of diabetic retinopathy (DR) services across Ghana remains paramount, there is currently a poor understanding of nationwide DR treatment services. This study aims to conduct a situation analysis of DR treatment services in Ghana and provide evidence on the breadth, coverage, workload, and gaps in service delivery for DR treatment. Methods A cross-sectional study was designed to identify health facilities which treat DR in Ghana from June 2018 to August 2018. Data were obtained from the facilities using a semi-structured questionnaire which included questions identifying human resources involved in DR treatment, location of health facilities with laser, vitreoretinal surgery and Anti-vascular endothelial growth factor therapy (Anti-VEGF) for DR treatment, service utilisation and workload at these facilities, and the average price of DR treatment in these facilities. Results Fourteen facilities offer DR treatment in Ghana; four in the public sector, seven in the private sector and three in the Christian Health Association of Ghana (CHAG) centres. There was a huge disparity in the distribution of facilities offering DR services, the eye care cadre, workload, and DR treatment service (retinal laser, Anti-VEGF, and vitreoretinal surgery). The retinal laser treatment price was independent of all variables (facility type, settings, regions, and National Health Insurance Scheme coverage). However, settings (p = 0.028) and geographical regions (p = 0.010) were significantly associated with anti-VEGF treatment price per eye. Conclusion Our results suggest a disproportionate distribution of DR services in Ghana. Hence, there should be a strategic development and implementation of an eye care plan to ensure the widespread provision of DR services to the disadvantaged population as we aim towards a disadvantaged population as we aim towards a universal health coverage.